Description of silent nature in the letters of the first Mamluk era: The book (Shtouiat) by Ibn Fadl Allah Al-Omari (749 HIJ) as an example - Muhsen, Ali (Al-Adab Journal, 2024)
The art of Diwaniyah and Brotherhood letters formed an important pillar in the code of Arabic literature, and it grew during the Abbasid era and became his specific rules and structure, and Manal poetry has changed it, it has been weighed down by costliness and artificiality Badi'I.     The writers of the Mamluk era have walked in different directions to develop this art, and many works have emerged to establish it, and Ibn Fadl Allah Al-Omari is the most prominent flags of artistic writing in the first Mamluk era in theory and application, and his book (Shtouiat) can be considered a distinctive model for the Brotherhood letters, it contains dozens of letters exchanged between Omari and writers and scholars of his time, so it reflects the extent to which the art of letters reached in the eighth century of migration.    The Shtouiat letters are characterized by their tendency to renew in the structure, most writers and scholars have exceeded the traditional and familiar conclusion, but these letters did not get rid of the constraints of cost and industry Badi'I.